Can Countries Learn from each Other? Navigating Change in Fisheries and Gleaning Lessons from Growth Stories of Bangladesh, India and Thailand - Suvetha Venkatachalapathi; Ananthan PS; Talib Mohammad; Neha W. Qureshi; Shivaji D. Argade (Journal of Indian Fisheries Association, 2024)
The fisheries play a vital role in the economy and food security of many Asian nations, especially Bangladesh, India and Thailand. This study analyses the growth of fisheries GDP, fish production, fish yield and export and import dynamics of the fisheries sector in Bangladesh, India and Thailand from 1991 to 2020. Developing economies witnessed a transformation in their GDP composition with steady decline of agricultural sector share. During 1991-2020, the agriculture sector's contribution to overall GDP declined from 34%, 32% and 15% in 1991 to 12%, 18% and 9% in 2020 in Bangladesh, India and Thailand, respectively. Within the agricultural sector, fisheries contribution increased gradually in Bangladesh and India, while it halved in Thailand from 2% to 1% due to a decline in fish production since 2001. One-way ANOVA revealed significant differences (p < 0.05) in fisheries GDP, production, exports and imports across the selected countries. Aquaculture production outpaced capture fisheries, with India exhibiting the highest marine fish yield growth but lagging in inland fish yield. Thailand initially led fisheries exports but experienced a decline after 2016, necessitating greater reliance on importing raw materials for value-added re-exports. Unlike Thailand and Bangladesh, India has lagged in improving per capita fish consumption during the period in spite of higher growth in fish production. Gleaning evidence and insights from the cross-country comparison, this study underscores the economic significance of fisheries and suggests key interventions to prioritize and reorient fisheries development policies to make them more sustainable and fastrack the attainment of SDG 2030 targets.